Pengaruh Penambahan Puree Daun Kelor (Moringa oleifera Lamk.) Terhadap Karakteristik Nugget Ikan Kembung (Rastrelliger kanagurta) - Puspa Hapsari, Komang Ayu; Sugitha, I Made; Suparthana, I Putu (Jurnal Ilmu dan Teknologi Pangan (ITEPA); Vol 11 No 1 (2022): Jurnal ITEPA, 2022)
This study aims to determine the effect of addition Moringa leaf puree on the characteristics of mackerel nuggets, and to find out the right addition of Moringa leaf puree to produce mackerel nuggets with the best characteristics. This research was based on completely randomized design (CRD) with by addition treatment of Moringa leaf puree consisting of 6 levels: 0%, 10%, 20%, 30%, 40% and 50%. Each treatment was repeated 3 times to obtain 18 experimental units. The data obtained were analyzed by variance and if the treatment had significant effect followed by Duncan Multiple Range Test (DMRT). The results showed that the effect of adding Moringa leaf puree had a significant effect on water content, fat content, protein content, crude fiber content, antioxidant activity, taste, aroma, texture (hedonic and scoring), and overall acceptance. The addition of 20% Moringa leaf puree produced with the best characteristics with water content criteria of 44,18%, ash content of 1.47%, fat content of 11.49%, protein content of 8.85%, crude fiber content of 9.26%, antioxidant activity of 67.32%, IC50 3757.486 ppm, ordinary aroma, taste like, texture and overall acceptance liked.